Analysis of Student Skills in Developing Mathematics Learning Videos Using ICT-Based Learning Media - Mujtahid, Zainul; Widya, Widya; Rahadi, Irwan; Sinaga, Nurul Afni (Hexagon: Jurnal Ilmu dan Pendidikan Matematika, 2024)
The development of ICT-based learning media can improve the quality of learning. The availability of ICT-based learning media is still limited, while the Merdeka curriculum demands the application of ICT-based learning media in learning. Therefore, prospective teachers must be equipped to develop ICT-based learning media, one of which is learning videos. The type of research is a case study with 29 research subjects (students/prospective teachers) from the mathematics education study program at Malikusaleh University. Data collection is carried out through assessing learning videos made by students. Then, the assessment data is analyzed using a student skills analysis sheet in creating/designing a learning video. The assessment results show that students have reached the "Very Skilled" level in the indicators: the material is presented coherently and systematically, the language used is easy to understand, and the media delivery strategy makes it easier to understand and master the material. Students also reach the "Skilled" level in indicators: delivering material with correct intonation and precise articulation, learning the material presented, and having excellent and appropriate time management in providing the material. However, there are several differences in the results of assessing students' levels by the three assessors on the indicators: media used for the material taught, effective and efficient use of learning media, creativity in learning media and learning media used.